The effects of static stretching on speed and agility: One or multiple repetition protocols? - Avloniti, A.; Chatzinikolaou, A.; Fatouros, I. G.; Protopapa, M.; Athanailidis, I.; Avloniti, C.; Leontsini, D.; Mavropalias, G.; Jamurtas, A. Z. (European Journal of Sport Science, 2016)
Although static stretching (SS) is utilized during warm-up before training and competition, the results about its effects on performance remain controversial. We examined whether performing a stretch of short-to-moderate duration (<60 sec) in a single repetition produces a similar or different effect on speed and agility performance from the effect which is produced while performing the same stretch in multiple repetitions of the same total duration. According to a repeated measurement design, 40 trained males were randomly assigned to either (1) a single repetition group or (2) a multiple repetition group. The participants in each group performed five trials: a control trial (no stretches were performed) and four experimental trials of SS protocols consisting of five exercises performed at either 20 sec (2 × 10 in the second group), 30 sec (3 × 10 in the second group), 40 sec (4 × 10 in the second group) or 60 sec (6 × 10 in the second group) of total duration. A two-way repeated measures analysis of variance showed that the participants in both group improved their speed performance in response to the 20-sec trial, whereas agility remained unaffected. Data analysis also revealed that the repetition number did not affect speed and agility performance. These data suggest that SS of short duration (<30 sec) may actually improve acute speed performance, whereas SS of moderate duration may not hamper speed and agility performance. Moreover, the effects of SS protocols are related to the total duration of each exercise and not to the number of repetitions in which each exercise is performed.